Hosting elite sport events to target recreational sport participation: an interrupted time series analysis - Mölenberg, F. J. M.; de Waart, F.; Burdorf, A.; van Lenthe, F. J. (International Journal of Sport Policy and Politics, 2020)
Increasing sport participation by hosting elite sport events is a much-debated policy. This study evaluated the effect of hosting elite sport events on sport participation against the background of a shift in focus towards targeting recreational sport participation. We included 10 international elite sport events organised between 2000 and 2017 in the city of Rotterdam, the Netherlands. Sport-specific participation in the pastyear was obtained from abiannual cross-sectional survey. Per event, interrupted time series analyses were employed using 3 pre- and post-event measures. Data were summarised by means of random-effects meta-analyses. We tested for group differences to evaluate if events organised in the period with amore explicit aim to target recreational sport participation, and associated policies, had a larger impact. Three events concerning cycling, table tennis and gymnastics were followed by an increase in sport-specific participation 1-year after the event was organised, whereas the korfball event was followed by adecrease. The pooled effect of the 10 events did not show any change in sport-specific participation (0.2%-point (95% CI: -0.3; 0.8)). Significant group differences by period were found. More recent events targeting sport participation were followed by an increase in sport-specific participation (1.1%-point (95% CI: 0.0; 2.1)), but not for other events (-0.3%-point (95% CI: -0.6; 0.1)). No group differences were found for the number of visitors and location. Hosting elite sport events that explicitly target sport participation may increase sport participation among citizens. Longitudinal data following individuals over time are needed to support this finding.